Hasil Belajar Dalam Kemampuan Analisis (C5): Implementasi Model Pembelajaran Flipped Clasroom - Dio Fransisca; Farida Farida; Robiyah Nur (Prodi Pendidikan Keagamaan Islam, 2026)
This study is motivated by the low learning outcomes of students in Islamic Religious Education (PAI) at SMP Negeri 36 Bandar Lampung, particularly at the C5 cognitive level (evaluating). The main factors contributing to this issue include low learning motivation, limited student participation, and the use of conventional, non-interactive teaching methods. Therefore, this study aims to examine the effectiveness of the Flipped Classroom learning model in improving students’ learning outcomes. This research employs a quantitative method with a quasi-experimental approach and a post-test only control group design. The population consists of all seventh-grade students, with samples selected through cluster sampling using the spin-the-wheel method. Class VII G is designated as the experimental group, while class VII B serves as the control group. The experimental group studies independently at home using instructional videos and engages in interactive discussions in class, whereas the control group receives conventional instruction. Students’ learning outcomes are measured using a multiple-choice test targeting the C5 level and analyzed using the Mann–Whitney test.